PENDIDIKAN PEREMPUAN RIAU DARI MASA KE MASA - Wilaela Wilaela (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
The existence of woman education instituation in Riau province has long history, far away before the existence of Riau as a province. The history can be divided into period of Dutch colonial, Japanese colonial till the period of independence. Every period has individuality differentiating from other period. Latifah School and of Madrasah Annisa in the empire of Siak in the period of colonization differ from Diniyah Putri Pasirpangaraian, YKWI and Diniyah Putri in Pekanbaru in the period of independence. However, there was a similiarity among the periods, that is the characteristic of woman education which had lifted the ability and role of woman as the primary and first educator and teacher, either in or out of the house, in the society, and in the school. The study also found that in each period, the woman education instituation in Riau has a relationship to Diniyyah Puteri Padang Panjang.